Norma i uzus w dydaktyce przekładu specjalistycznego wobec oczekiwań rynku pracy - Jokiel, Małgorzata (Investigationes Linguisticae, 2019)
The author focuses on issues related to university teaching of interpretation and translation: consecutive interpretation and sight translation in respect of a specialist language, in particular the economic one. The starting point for further considerations is the presentation of the characteristics of the above-mentioned specialist language and the question regarding the role and importance of specialist knowledge and quality criteria in the process of interpretation and translation teaching. From the viewpoint of author’s own teaching and practical experience, an attempt is made to diversify priorities, goals and methodological approaches in relation to the above-mentioned forms of interpretation and translation. Market requirements and expectations of potential employers, resulting from job advertisements, become of a particular importance in this context, as they need to be taken into consideration in order to optimize teaching of interpretation and translation.